Improving the Quality of Coconut Fruit (Cocos nucifera L.) by Adjusting Planting Age - Eko Wahyudi; M. Amrul Khoiri; Qory Fadillah Cahya; Anthony Hamzah; Rizki Al Khairi Barus (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Coconut (Cocos nucifera L.) is a strategic plantation crop in Indonesia, playing important roles in society, the economy, and industry. Indragiri Hilir Regency is the largest producer of coconut in Riau Province; however, productivity has declined as plantations have aged. This study aimed to analyze the quality of coconut fruit based on plant age. A non-experimental comparative observational design was employed with three plant age treatments (15, 20, and 25 years). Each treatment was replicated six times, yielding 18 experimental units. Each unit consisted of two sample plants, totaling 36 plants. The measured parameters included endosperm thickness (mm), oil yield (%), and oil moisture content (%). For oil yield and moisture analysis, two mature coconuts were collected from each plant and analyzed in the laboratory, resulting in 36 samples. Data were analyzed using one-way ANOVA, and significant results were further tested using Tukey's HSD at the 5% level. The results showed that plant age had a considerable effect on endosperm thickness, oil yield, and moisture content. These findings suggest that plant age affects coconut fruit quality, with 25-year-old trees producing the highest-quality fruits in the Tembilahan Hulu District, Indragiri Hilir Regency. This study offers recommendations for coconut farmers to optimize cultivation strategies, thereby enhancing production and fruit quality.